Correlations among four measures of thoracic kyphosis in older adults. Issue 3 (March 2016) - Tran, T.; Wing, D.; Davis, A.; Bergstrom, J.; Schousboe, J.; Nichols, J.; Kado, D.
Abstract Summary There are many ways to measure thoracic kyphosis ranging from simple clinical to more complex assessments. We evaluated the correlation among four commonly used kyphosis measures: Cobb angle, Debrunner kyphometer, kyphotic index, and the blocks method. Each measure was correlated with the others, confirming high clinical and research applicability. Introduction The purpose of this study was to assess the associations among four commonly used measures of thoracic kyphosis in older adults. Methods Seventy two men and women aged 65–96 were recruited from the San Diego community. Four kyphosis measures were assessed in the same person during a baseline clinic visit. Two measures were done in the lying (L) and two in the standing (ST) position: (1) Cobb angle calculated from dual X-Ray absorptiometry (DXA) images (L), (2) Debrunner kyphometer (DK) angle measured by a protractor (ST), (3) kyphotic index (KI) calculated using an architect's flexicurve ruler (ST), and (4) the blocks method involving counting the number of 1.7 cm-thick blocks required to achieve a neutral head position while lying flat on the DXA table (L). Spearman rank correlation coefficients were used to determine the strength of the association between each kyphosis measure. Results Using the Cobb angle as the gold standard, the blocks method demonstrated the lowest correlation (r s = 0.63, p < 0.0001), the Debrunner method had a moderate correlation (r s = 0.65, p < 0.0001), and the kyphotic index had the highest correlation (r s = 0.68, p < 0.0001). The correlation was strongest between the kyphotic index and the Debrunner kyphometer (r s = 0.76, p < 0.0001). Conclusion In older men and women, all four measures of thoracic kyphosis were significantly correlated with each other, whether assessed in the lying or standing position. Thus, any of these measures demonstrate both potential clinical and research utility.